エンチョク セキブン ウンスイ リョウ ノ ミツモリ - 和田, 誠; ワダ, マコト; Wada, Makoto (1991)
P(論文) 南極域における気候変動に関する総合研究計画が1987年から開始された。この計画の主テーマの一つが雲と降水の観測である。雲と降水を考える上で, 大気中の液体の水の量(雲水量), 固体の水の量(氷水量)は重要な量であるが, 測定が難しく観測例が少ない。今回の観測期間中の氷水量については, 気象レーダー観測から求めることができた。一方雲水量は, マイクロ波放射計の観測から求めた。しかし放射計の性能の問題, 低温での使用上の問題等のため絶対値を正確に求めるためにはデータの質を吟味しながら, 十分な処理をしなければならない。今回冬7月と春(10)月のケースについて, 2波長の放射計から得られた値を比較することによって, かなり信頼度の高い結果が得られたので, その方法を紹介する。この結果から見て南極のような低温域では, 1波長の放射計からでもかなり信頼度の高い雲水量の値を求めることができると考えられる。 A 5-year project of "Antarctic Climate Research (ACR)" started in 1987. One of the main projects of the ACR is an observation of clouds and precipitation. Liquid water content and ice water content are important parameters for considering the characteristics of clouds and precipitation. Ice water content in the atmosphere has been calculated from the data of the vertical pointing radar observation. On the other hand, vertically integrated liquid water content can be estimated by the data of microwave radiometers. It is very difficult to estimate reliable values of vertically integrated liquid water content because of the ability of microwave radiometer in the cold regions, some noises on data recording and difficulty of data calibration. As to some case studies at Syowa Station in Antarctica most reliable values of vertically integrated liquid water contents could be estimated. Moreover, there is a possibility of estimation of vertically integrated liquid water contents in cold areas from careful analysis of data of a microwave radiometer. departmental bulletin paper